2019
DOI: 10.1159/000497072
|View full text |Cite
|
Sign up to set email alerts
|

Tollip Inhibits ST2 Signaling in Airway Epithelial Cells Exposed to Type 2 Cytokines and Rhinovirus

Abstract: The negative immune regulator Tollip inhibits the proinflammatory response to rhinovirus (RV) infection, a contributor to airway neutrophilic inflammation and asthma exacerbations, but the underlying molecular mechanisms are poorly understood. Tollip may inhibit IRAK1, a signaling molecule downstream of ST2, the receptor of IL-33. This study was carried out to determine whether Tollip downregulates ST2 signaling via inhibition of IRAK1, but promotes soluble ST2 (sST2) production, thereby limiting excessive IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…In human, Tollip has four isoforms, namely, isoform A, isoform B, isoform C, and isoform D ( 35 ). Tollip plays a critical role in regulating TLR-mediated innate immune responses ( 36 , 37 ). It was reported that Tollip interacted directly with TLR2 or TLR4 with its C-terminal domain (179–273 aa).…”
Section: Discussionmentioning
confidence: 99%
“…In human, Tollip has four isoforms, namely, isoform A, isoform B, isoform C, and isoform D ( 35 ). Tollip plays a critical role in regulating TLR-mediated innate immune responses ( 36 , 37 ). It was reported that Tollip interacted directly with TLR2 or TLR4 with its C-terminal domain (179–273 aa).…”
Section: Discussionmentioning
confidence: 99%
“…However, this might be different in other tissues such as lung epithelia. On the one hand, IRAK-1 was shown to be essential for IL-8 production in human airway epithelial cells [77]. On the other hand, IRAK-1 is necessary for the rhinovirus-stimulated induction of CXCL-10 in airway epithelial cells and macrophages [78].…”
Section: Discussionmentioning
confidence: 99%
“…Even though these early pro-inflammatory responses are necessary, they must be tightly regulated to prevent excessive inflammation and subsequent tissue damage. Dual specificity phosphatases, which inhibit various mitogen-activated protein kinase (MAPK), tollinteracting protein (Tollip), a negative regulator of TLR signaling pathway, and TLR2-activation mediated IRAK-1 degradation within a short period after RV infection may all contribute to limiting RV-induced inflammation (Unger et al, 2012;Manley et al, 2019;Dakhama et al, 2020).…”
Section: Replication-dependent and Independent Pro-inflammatory Respomentioning
confidence: 99%